Tożsamość i kondycja człowieka - Irena Grochowska (Studia Ecologiae et Bioethicae)
Human aims for internal integrity and unison at all levels of human are identity and all dimensions of human existence. According to Rull integrity is a gift from God, but also a task for everybody, only possible when a human being is open for autotranscendency. Unity of mankind is based on condition. The key word condition means that a human being is not neutral. The conditions indicates limitations and burdens of human being, although more and more frequently modern man tries to deny it, defining by himself who he wants to be and taking the place of God. Modern individualism is a lonely following of traditional utopia of society.